(untitled) (Research, Society and Development, 2022)
The study aimed to investigate the anthropometric profile of female beach volleyball athletes through a systematic review of the literature. For this, a careful bibliographic survey was carried out about mapping the scientific productions available in order to obtain reliable data on the investigated theme. Thus, we adopted as methodological criteria: identification, screening, eligibility and inclusion, using Boolean descriptors “AND”, “OR” and “NOT”, combining them in order to obtain the works relevant to the subject in question. It was possible to identify that there is a prevalence of ecto-endomorph profiles of athletes in the basic categories that are directed to an offensive positioning in the game, due to having a greater stature, strength and low %F, which corroborates with the attack positioning. The endo-mesomorph profile was affected as defensive positions, due to the prevalence of higher %F and having a smaller stature in relation to ecto-endomorphs. In short, we can observe that the anthropometric profile, as well as the body composition of beach volleyball athletes, is associated with the offensive and defensive positions in play.